Implementation of liquid chromatography tandem mass spectrometry for the analysis of ciguatera fish poisoning in contaminated fish samples from Atlantic coasts. (15th May 2019) - Estevez, Pablo; Castro, David; Manuel Leao, J.; Yasumoto, Takeshi; Dickey, Robert; Gago-Martinez, Ana
Highlights: LC-MS/MS allowed to confirm the presence of Ciguatoxins in fish from Atlantic coasts. The evaluation of the efficiency of sample pretreatment is critical. Caribbean Ciguatoxin-1 has been the main responsible for the contamination. This is the first identification of a hydroxy derivative of C-CTX1. Abstract: The increased emergence of Ciguatera Fish Poisoning in the Canary Islands and Madeira demanded the development of confirmatory methods by liquid chromatography coupled to tandem mass spectrometry to characterize the risk. Efforts were particularly focused on the optimization of sample pretreatment, especially in the sample cleanup step, to efficiently remove matrix interferences as a critical factor to consider in mass spectrometry detection. Two different LC-MS/MS approaches have been used for confirmation purposes, the first one using the sodium adduct as precursor and product ion to allow an increased sensitivity in the detection, whereas additional fragments were also monitored for further confirmation. The optimized conditions above mentioned allowed the confirmation of Caribbean Ciguatoxin-1 as the main responsible for the samples analyzed from these geographical areas, while the presence of a new hydroxyl metabolite of C-CTX1 was also confirmed in one sample analyzed in this study.